2021
DOI: 10.3390/su13042409
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Options for Noise Reduction from a Wastewater Treatment Plant: Case Study

Abstract: Industry and industrial complexes are often located in the proximity of people’s homes. One of the negative effects of industry is noise emissions into the surrounding environment. With the increasing concentration of the human population and the increase in industrial production, more and more people are exposed to the negative effects of noise. This article discusses a comprehensive approach to reducing noise emissions from industrial operations, and the subsequent impacts on surrounding villages and human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The authors [ 9 , 25 ] examined how the form walls affect the orientation factor in the case of steel fibres. In the case of rigid (steel) and flexible (synthetic) fibres, the effect of the formwork on the orientation of the fibres is different, because fibres of different materials [ 26 , 27 ] behave differently with respect to the formwork when in contact with the substrate. This different behaviour will be influenced by its effects on the number of fibres intersecting the cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [ 9 , 25 ] examined how the form walls affect the orientation factor in the case of steel fibres. In the case of rigid (steel) and flexible (synthetic) fibres, the effect of the formwork on the orientation of the fibres is different, because fibres of different materials [ 26 , 27 ] behave differently with respect to the formwork when in contact with the substrate. This different behaviour will be influenced by its effects on the number of fibres intersecting the cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses are carried out in line with numerical simulations in the process of strategic noise mapping and action plans. In the literature, various noise mapping software are used in noise mapping simulations and it is observed that the most widely used noise mapping programs are SoundPLAN [ 12 , 14 , 17 , 18 , 23 , 25 , 47 – 50 ], CadnaA [ 15 , 19 21 , 51 , 52 ], and Predictor [ 16 , 36 , 53 ]. In the research of Butorina et al [ 12 ], SoundPLAN noise mapping software was used to analyze noise level, increasing the efficiency of the noise protection design process was carried out with the application of building information modeling (BIM).…”
Section: The Strategic Noise Mapping Process Based On Industrial Noisementioning
confidence: 99%
“…It was stated that some of the usual techniques for control of sound in the transmission path are mufflers, vibration insolation, break mechanical paths, increasing the transmission paths, use of sound absorptive materials, and construction of heavy airtight enclosures. In the research of Moravec et al [ 51 ], noise reduction from a wastewater treatment plant was explained. Noise reduction in wastewater plants was achieved by means of the replacement of ventilation grilles with acoustic blinds and the providing the acoustic insulation of air distribution pipes.…”
Section: The Improvement Of Environmental Qualitymentioning
confidence: 99%
“…A number of factors that may affect hearing loss are known, for example race, gender, age [21,22], smoking [23,24], hypersensitivity to noise [25], previous noise exposure [26,27], hypertension [28], synergistic effects [29], and others. An important step in assessing the effects of noise is also proposing measures to reduce it; Moravec et al (2017Moravec et al ( , 2021 [30,31]. Employees who are exposed to hand and arm vibrations are also exposed to high noise levels.…”
Section: Some Important Occupational Diseasesmentioning
confidence: 99%